MANAJEMEN RISIKO TAHAP KONSTRUKSI PEKERJAAN PENINGKATAN JARINGAN IRIGASI DAS (DAERAH ALIRAN SUNGAI) TUKAD SUNGI DI KABUPATEN TABANAN - I Nyoman Norken; Kadek Diana Harmayani; Ni Putu Indah Yuliana (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2019)
RISK MANAGEMENT AT THE CONSTRUCTION STAGE OF IMPROVING THE IRRIGATION NETWORK OF THE SUNGI RIVER WATERSHED AREA IN TABANAN REGENCY ABSTRACT The implementation of irrigation network improvement project in Sungi River Watershed is quite complex because it is related to water regulation system by water user farmer association (subak). In the implementation there are various risks that may affect the cost, quality and timing of the project. The purpose of this study was to identify risks, assess and determine the acceptance of risk, determine the dominant risk and mitigation actions and risk ownership for the dominant risk. The research was conducted in the Irrigation Areas (IA) of Cangi, Bunyuh, and Baru Kedokan with a combination method (quantitative and qualitative descriptive). The data collection was done by distributing questionnaires to respondents directly involved in the project implementation. The number of respondents was 20 people and selected by purposive sampling. The results showed identified risks of 36 risks with 14 risks of previous research outcomes and 22 risks from brainstorming results. The risk assessment and acceptance results were categorized as undesirable 52.78%, acceptable 33.33%, negligible 13.89%, and no risk was found in the category of unacceptable. Mitigation was conducted on the undesirable risks by making changes to the initial design plan in accordance with the field conditions, intensifying the implementation of the supervision in the field and carrying out the work in accordance with the operational standards and procedures contained in the contract. The ownership of risk was allocated to the parties involved in the project implementation including job owners 8 risks, supervisory consultants 9 risks, contractors 16 risks and farmer community 1 risk. The undesirable risk should be the concern of the parties involved in the project so that the final results of the work were in accordance with quality, cost, and time planned.